Surface morphology of submicron crystals in aluminum nitride films grown by DC magnetron sputtering - P. Limsuwan (2018)
Aluminium nitride (AlN) thin films were fabricated on a glass substrate by reactive magnetron sputtering. Raman microscopy was then employed to follow the characteristics of their optical and acoustic phonon modes. At the optimal sputtering time of 30 minutes, the defect-induced first and second order Raman spectra, were observed in 400-800 cm-1band which were mostly related to the coating compositions. However, at the 30-, 60-and 90-minute sputtering, crystals of submicron size order of AlN were achieved. This could be clearly identified by the presence of Raman peak at 658-662 cm-1. Powder X-ray diffraction (PXRD) patterns revealed the development of (002) and (101) planes of hexagonal wurtzite AlN phase. The optimal average grain size measured by atomic force microscopy (AFM) is at 330 nm. It was found that the hardness was strongly dependent on roughness of the film, the maximum of which was achieved at 20.00 GPa. The presence of F-type defects in AlN films was investigated by X-band (∼ 9.44 GHz) ESR spectrometer at 295 K. The ESR experiments were carried out by applying magnetic field perpendicular to AlN film, which showed the ESR six-peak multiplet signal at ∼ 290 mT arising from superhyperfine interactions between nuclear spin I = 5/2 of27Al and electron spins trapped in nitrogen vacancies. The ESR signals are simulated and the ESR parameters are calculated. The vacancies are clearly randomly distributed as the ESR signals are independent of rotation angle (φ) about the normal of the film. All these results were analyzed and presented as a, function of the deposition parameters and composition, and crystalline phases existed in the films. © World Scientific Publishing Company.